Pengaruh Lama Perendaman dalam Obat Kumur Terhadap Kekerasan Polyethylene Fiber-Reinforced Composites - Afra Hatim; Widowati Siswomihardjo; Siti Sunarintyas (Jurnal Material Kedokteran Gigi, 2018)
Fiber-reinforced composites (FRC) is a resin base material that strengthen with fiber. In dentistry, these materials interacts with various fluid, such as mouthwash. Mouthwash that contains alcohol affects the physical and mechanical properties of the material. The aim of this research is to determine the effect of immersion duration in mouthwash towards the hardness of polyethylene fiber reinforced composites. The materials used in this research are polyethylene (Fiber UHMWPE, Vactrise), composite resin (MasterFlow, Brazil), and mouthwash (Original Listerine® Antiseptic). Strip-shaped specimens (5x2x2)mm is light cured for 20 seconds. The specimens is divided into K1 (control group), K2 (immersed for 24 hours) and K3 (immersed for 48 hours). Hardness values is measured using Vickers Hardness Test (Buehler, Germany). The data obtained is analyzed using one way anova and followed by LSD test. The results showed the mean of hardness of groups immersed with mouthwash (0, 24, and 48 hours) are 19±0.82 VHN, 14.33±0.25 VHN, and 8.67±0.84 VHN respectively. One way anova test showed there is a significant effect (p<0,05) of immersion duration in mouthwash towards the hardness of polyethylene FRC. LSD test showed significant differences between all groups. The conclusion of this research is prolonged immersion in mouthwashes decreases the hardness of polyethylene FRC.